A combined school survey and reactive case detection reveals minimal local transmission of malaria in the Highlands Region of Papua New Guinea - Osama Seidahmed; Serah Kurumop; Elizabeth Wawaga; Melvin Kualawi; Valentine Siba; Sharon Jamea; Yangta Ura; Leo Makita; William Pomat; Manuel W. Hetzel (Malaria Journal)
Abstract Background The Highlands of Papua New Guinea are non-endemic for malaria compared to the rest of the country. This study aimed to explore the local transmission of malaria in the Highlands through a cross-sectional school survey coupled with reactive case detection. Methods Between July and November 2019, 5575 schoolchildren and 1048 household members were screened for malaria using Rapid Diagnostic Tests, subsequently validated by light microscopy. In addition, an analysis of malaria cases (2017 to 2019) was conducted across 33 health facilities within the catchment areas of the surveyed schools and households. Results Thirteen individuals were diagnosed with malaria: eleven with Plasmodium falciparum (five schoolchildren, six household members) and two with Plasmodium vivax (one student, one household member); all were aged ten years or older. Malaria prevalence was 0.09% [95% CI 0.03, 0.3] among schoolchildren and 1.7% [95% CI 0.3, 9.1] among household members. Eleven positive individuals (84%) reported recent travel, mainly to lower-altitude endemic areas. Long-Lasting Insecticidal Nets were used by 34.8% [95% CI 28.7, 40.8] of household members. The average annual malaria incidence in the catchment areas was 3.7 cases per 1000 [95% CI 2.6, 5.3] among the general population, while children under 15 years accounted for 19% [95% CI 14, 27] of the positive cases. Conclusions Local malaria transmission appears to be minimal in the surveyed Highlands areas. Strengthening surveillance-response system to control imported cases and stop local foci could support malaria elimination in PNG. However, effective operational triggers for reactive case finding remain to be determined.